The Influence Of Word Of Mouth And Customer Trust On Purchase Interest For Kopi Siloka Products Among Generation Z In Tasikmalaya: - Kuraesin, Sara; Pauzy, Depy Muhamad; Yuniar, Evilia Sri (Utami Publisher, 2025)
This study aims to determine the effect of Word of Mouth and Customer Trust on Purchase Interest in Kopi Siloka Products among Generation Z in Tasikmalaya. The method used is quantitative with a research sample of 200 respondents. The data used are primary and secondary data. The analysis tool used in this study is multiple linear regression analysis using SPSS version 26. Based on the results of this study, it shows that Word of Mouth and Customer Trust simultaneously have a positive and significant effect on Purchase Interest in Kopi Siloka Products among Generation Z in Tasikmalaya. Word of Mouth partially has a significant effect on Purchase Interest. Customer Trust has a significant influence on Purchase Interest.